2020
DOI: 10.1371/journal.pone.0229917
|View full text |Cite
|
Sign up to set email alerts
|

Community gender systems and a daughter’s risk of female genital mutilation/cutting: Multilevel findings from Egypt

Abstract: We tested a feminist social-ecological model to understand community influences on daughters' experience of female genital mutilation/cutting (FGMC) in Egypt, where over 90% of women ages 15-49 are cut. FGMC has potential adverse effects on demographic and health outcomes and has been defined as a human-rights violation. However, an integrated multilevel-level framework is lacking. We theorized that a more favorable community-level gender system, including stronger gender norms opposing FGMC and expanded extra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Consistent negative association has been reported between women’s education, FGM/C intention and its perpetration [ 26 30 ]. The common pathways for the negative association include the fact that education enlightens women to appreciate the consequences of FGM/C on females’ sexual and reproductive health [ 28 ] including mental health implications [ 31 ].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Consistent negative association has been reported between women’s education, FGM/C intention and its perpetration [ 26 30 ]. The common pathways for the negative association include the fact that education enlightens women to appreciate the consequences of FGM/C on females’ sexual and reproductive health [ 28 ] including mental health implications [ 31 ].…”
Section: Introductionmentioning
confidence: 64%
“…The common pathways for the negative association include the fact that education enlightens women to appreciate the consequences of FGM/C on females’ sexual and reproductive health [ 28 ] including mental health implications [ 31 ]. Education in effect empowers women to oppose all forms of violence against women and protect their children from experiencing FGM/C and abuse of all forms [ 30 , 32 ]. Meanwhile, Hayford et al [ 33 ] observed that daughters of women with primary or higher education experienced FGM/C in Burkina Faso, Cote d’voire, Guinea and Mali.…”
Section: Introductionmentioning
confidence: 99%
“…The contextual factors were place of residence (urban or rural), community literacy level-proportion of women who can read and write (low, medium, high) and community socio-economic status-proportion of women in the richest household quintile (low, medium, high). The selection of these variables was influenced by their associations with FGM in previous studies [11,12,[14][15][16].…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…As another example, female genital mutilation/cutting is often tied to gender norms regarding femininity, purity, cleanliness and control of female sexuality. As a collective practice, it serves to support and affirm normative expectations of women being sexually modest and appealing 14. Further, this practice is associated with detrimental health effects, including greater odds of contracting sexually transmitted diseases15 and adverse obstetric outcomes 16…”
Section: Gender Norms: Important Determinants Of Healthmentioning
confidence: 99%